Programmable Automation Controller Mechatronic Experiment - Thomas Gross; Kevin Anderson; Nolan Tsuchiya (Institute of Advanced Engineering and Science, 2017)
This paper describes the use of the OPTO-22 Programmable Automation Controller (PAC) Learning center in the undergraduate control systems course at California State Polytechnic University at Pomona (Cal Poly Pomona). The OPTO-22 PAC System is an integrated system of hardware and software used for industrial control, remote monitoring, and data acquisition applications. The paper compares the pros and cons of using a PAC versus Programmable Logic Controller (PLC) or Field Programmable Gate Array (FPGA) systems. The paper introduces the flowchart based programming environment used in PACs. The paper includes an illustrative example of how the OPTO-22 PAC system can be interfaced to an industrial based Mechatronics pick-and-place robot station. This example details the input/output interfaces of the OPTO-22 PAC unit and the SUN Equipment Mecahtronics pick and place robot unit. Details of the flow chart programming and I/O interfacing protocols are given in the paper. The I/O configuration dialog in the OPTO-22 PAC development environment are also presented in this paper.